What Do Elementary Students Need to Excel in English Learning? - Sinta Muchlis; Ardi, Havid (VELES Voices of English Language Education Society, 2024)
Integrating digital and interactive learning methods is crucial in enhancing English language acquisition among young learners. This study explores the preferences and attitudes of fifth-grade students toward these methods in English as a Foreign Language (EFL) education. The research aimed to identify the specific needs of young EFL learners and assess the effectiveness of technology-oriented learning models. A questionnaire was administered to 84 fifth-grade students, examining their engagement with various digital tools, including videos, audio materials, interactive games, digital modules, and mobile accessibility. The results indicate a strong preference for visually engaging and interactive methods, with students strongly inclined toward video-based learning and interactive activities, particularly enjoying interactive games. Digital modules with interactive exercises, quizzes, and simple, user-friendly layouts were highly favoured, and colourful transitions and animations further enhanced their experience. The study also highlights the demand for responsive, mobile-accessible modules and tools that provide progress tracking and feedback. These findings underscore the importance of incorporating multimedia and interactive elements in EFL resources to better cater to the needs of young learners, suggesting that digital methods can significantly improve language acquisition and student engagement.